Comparative study of lactate removal in short term massage of extremities, active recovery and a passive recovery period after supramaximal exercise sessions - Gupta, S.; Goswami, A.; Sadhukhan, A. K.; Mathur, D. N. (International Journal of Sports Medicine, 1996)
This investigation highlights the comparison of blood lactate removal during the period of recovery in which the subjects were required to sit down as a passive rest period, followed by active recovery at 30% VO(2)max and short term body massage, as the three modes of recovery used. Ten male athletes participated in the study. Exercise was performed on a bicycle ergometer with loads at 150% VO(2)max, each session lasting 1 min, interspaced with 15 sec rest periods, until exhaustion. Blood lactate concentration was recorded at recovery periods of 0,3, 5, 10, 20, 30, and 40 min, while VO(2), VCO(2) and heart rate were recorded every 30 sec for 30 min. The highest mean lactate value was found after 3 min of recovery irrespective of the type of modality applied. Significantly lower half life of lactate was observed during active recovery (15.7 +/- 2.5 min) period, while short term massage as a means of recovery required 21.8 +/- 3.5 min and did not show any significant difference from a passive type of sitting recovery period of 21.5 +/- 2.8 min. Analysis of lactate values indicated no remarkable difference between massage and a passive type of sitting recovery period. It was observed that in short term massage recovery, more oxygen was consumed as compared to a passive type of sitting recovery. It is concluded from the study that the short term body massage is ineffective in enhancing the lactate removal and that an active type of recovery is the best modality for enhancing lactate removal after exercise.